A rare case of sporadic Creutzfeldt-Jakob disease in an 83 years old female - Kuotsu, Medo M.; Kallupurakkal, Arjun Bal; Konyak, Nyamnyei; Chanu, Keisham Jaya; Khruomo, Vikie-o; Perumal, Dinesh Kumar (International Journal of Advances in Medicine, 2021)
Sporadic Creutzfeldt-Jakob disease is a rare invariably fatal neurodegenerative prion disease. Prion disease are associated with the conversion of alpha-helix rich cellular prion protein (PrPC) into a beta-structure rich insoluble conformer scrapie isoform (PrPSc) thought to be infectious isoform. Here we present a case of an 83 years old woman with findings of rapidly progressive dementia, cognitive disturbance, myoclonic jerks and extrapyramidal signs (cogwheel rigidity). Following a series of clinical and diagnostic (diffusion-weighted magnetic resonance imaging (MRI) brain, electroencephalogram (EEG)) examination she was diagnosed with sporadic Creutzfeldt-Jakob disease based on Centers for disease control and prevention (CDC) criteria.